Vliv polysacharidů na imunitní buňky a hojení ran - Franková, Jana, 1977- (2006)
Polysaccharides are high molecular weight condensation polymers with tens and often hundreds of monosaccharides residues per polysaccharide chain. These biomolecules perform a number of different functions in living organisms. Some polysaccharides act as structural components, for example, in the cell walls of plants, some are food reserve and some serve as lubricating agents in joints. In this thesis we studied two types of polysaccharides: hyaluronan and D-glucans. Hyaluronan is an acidic polysaccharide consisting of a disaccharide repeat unit of D-glucuronic acid and N-acetyl-D-glucosamine. It is a water solution, which is very viscous even at low concentration. In spite of its high viscosity it is capable reacting with a wide range of biomolecules including tissue components, proteins, proteoglycans and growth factors. It is the ability of hyaluronan to interact and to recognise and to be recognised by other biological molecules, which makes it a potential use in the area of tissue.